Wind tunnel tests on a generic eurocopter 350Z helicopter - Ishak, Iskandar Shah; Mat Lazim, Tholudin; Mansor, Shuhaimi (2008)
This paper summarizes a wind tunnel investigation on the aerodynamics characteristic of a rigid 14% model of a hybrid Eurocopter helicopter. The test was conducted in the 2m x 1.5m Universiti Teknologi Malaysia - Low Speed Tunnel (UTM-LST). The model, supplied by Eurocopter France, is equipped with a high torque motor that can rotate the main rotor up to 900 rpm during wind-on condition. The aerodynamic loads measurements were made using a 6-components external balance, which is capable to determine 3 aerodynamics forces and 3 aerodynamics moments. As the aerodynamic loads vary with pitch and yaw angle, the wind tunnel test was performed in the range of -10o to +10o of pitch and yaw angles, respectively. The selected test wind speed was 40 m/s, which corresponds to a Reynolds number of 3.7 x 106. To note the effects of main rotor rotation on the aerodynamic loads, the test was carried out ‘with’ and ‘without’ main rotor rotation. Given that the model had previously been tested, with participation of UTM Aerolab staffs, at Marignane Wind Tunnel, France in April 2006, results comparison could be made for this two different type tunnels since UTM-LST is a closed circuit-returned type tunnel, whereas Marignane Wind Tunnel is an open test section Eiffel type wind tunnel with semi guided air-returned with a free test section of 3m diameter and 2.7m length. In addition, test was also conducted without the tail part to investigate the lateral and longitudinal stability of this helicopter model.